Evaluate: m=((-3)-5)/((-5)-(-3))

Expression: $m=\frac{ \left( -3 \right)-5 }{ \left( -5 \right)-\left( -3 \right) }$

Remove unnecessary parentheses

$m=\frac{ -3-5 }{ \left( -5 \right)-\left( -3 \right) }$

Remove unnecessary parentheses

$m=\frac{ -3-5 }{ -5-\left( -3 \right) }$

When there is a $-$ in front of an expression in parentheses, change the sign of each term of the expression and remove the parentheses

$m=\frac{ -3-5 }{ -5+3 }$

Calculate the difference

$m=\frac{ -8 }{ -5+3 }$

Calculate the sum

$m=\frac{ -8 }{ -2 }$

Cancel out the common factor $-2$

$m=4$